DYSKUSJA W ŚRODOWISKU «THEMIS POLSKIEJ» NAD PRZYWRÓCENIEM TRYBU KASACYJNEGO W SĄDOWNICTWIE NAJWYŻSZYM KRÓLESTWA POLSKIEGO (1828-1830) - Pomianowski, Piotr (Zeszyty Prawnicze, 2017)
Discussion on the cassation’s restoration in the Congress Kingdom of Poland in the First Polish Legal Journal «THEMIS POLSKA» Summary Themis Polska was edited between 1828 and 1830 in Warsaw by young and well-educated lawyers. One of the main subjects discussed in this journal was a restoration of the cassation in the Congress Kingdom of Poland, a country which was dependent on the Russian Empire. An autocratic Tsar of Russia was simultaneously a King of Poland which was formally a constitutional state. In the course of time Tsar continued to limit Poland’s constitutional rules. At the end of the 1820s Polish lawyers postulated a return of the cassation, an institution which restrains power of a sovereign. Cassation functioned in Poland during a French domination (in the Duchy of Warsaw) in the same form as it did in France. The aim of this institution was to separate a protection of obedience to the laws (as a competence of the Court of Cassation) from bringing in new verdicts in individual cases (as a competence of lower courts). Plans to restore the cassation was interrupted by the November Uprising (1830-1831).